TOLERANSI DALAM KEHIDUPAN SOSIAL BERAGAMA - Umi Hasanah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2017)
Apart from being social beings, humans are also creatures who need and believe in God, the concept of God here is not only Allah. Because the conditions of the Indonesian people are plural, both in terms of language, ethnicity, and religion. Therefore God who is worshiped by its inhabitants is homogeneous. Thus, as fellow religious people must tolerate each other, in order to uphold the ukhuwah. This type of study is library research, which is an attempt to obtain data using library sources. The results of this study are that Tasamukh according to language means tolerance, while according to the term means respecting others. The essence of tasamukh is to maintain a personal stand but still be willing to accept the opinions of others, from all walks of life, be they religion, culture, social conditions, nationality and society